2013
DOI: 10.1177/0021998313480980
|View full text |Cite
|
Sign up to set email alerts
|

Fatigue failure of printed circuit board chemically etched copper traces in multifunctional composite structures

Abstract: One class of multifunctional composite structures is one that is capable of load-bearing while transferring electrical current across a given span. An example is large antenna systems integrated into composite skins of aircraft and spacecraft. Current aircraft missions that require large amounts of sensing equipment can potentially involve heavy and bulky wiring systems. The bulk and mass inefficiency of these systems can be avoided by using multifunctional structures that mimic printed circuit boards to carry… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 18 publications
0
1
0
Order By: Relevance
“…A printed circuit board (PCB) fabrication of two narrow copper etched tracks was examined for its fatigue life in [129]. This process was proposed for multifunctional structures as it is made from a glass/epoxy composite material.…”
Section: Testing and Validationmentioning
confidence: 99%
See 1 more Smart Citation
“…A printed circuit board (PCB) fabrication of two narrow copper etched tracks was examined for its fatigue life in [129]. This process was proposed for multifunctional structures as it is made from a glass/epoxy composite material.…”
Section: Testing and Validationmentioning
confidence: 99%
“…This process was proposed for multifunctional structures as it is made from a glass/epoxy composite material. The embedded copper traces exhibited robust behavior compared to those traces laminated onto the surface of the material [129]. The authors investigated the copper fracture mechanism and concluded that cracks were being formed on the composite surface which then propagated through the copper trace causing electrical failure.…”
Section: Testing and Validationmentioning
confidence: 99%
“…1 The results they obtained allowed them to conclude that in order to stop crack growth the integrity of the coppercomposite interface must be assured. Kim and Gonzales 19 attempted to determine the effects of a cyclic traction load on fatigue behavior in a multifunctional system. Their study showed that cracks in copper do not necessarily form under stress concentration; rather, they were the result of propagation of cracks initiated inside the composite.…”
Section: Introductionmentioning
confidence: 99%